The Effectiveness of Mathematics Learning in HOTS-Based Student Mathematics Learning Planning - Sri Wahyuni; Ellis Mardiana Panggabean; Feri Haryati (Budapest International Research and Critics University, 2022)
The lesson plan is very important to be mastered by the teacher to be able to carry out learning in the classroom to be directed. The lesson plan also contains a question instrument as an assessment of the achievement of learning indicators. The questions compiled must contain high-level thinking-based questions in this 4.0 century. However, in reality, many teachers have difficulty compiling lesson plans with high-level thinking questions. Student teacher candidates also have not been able to design high-level question-based questions. This study aims to see the effectiveness of mathematical literacy in planning student mathematics learning based on HOTS. This research is qualitative research using research methods in the form of data analysis of research results about HOTs that have been designed, interviews, and documentation. The results of this study indicate that the average value of students in planning HOTs-based mathematics learning is 85.7%. Then based on the HOTs-based learning planning that has been designed, 77.8% of students have been able to design questions and their answers by applying questions in everyday life and designing open-ended questions.